Hand tools - Skills education Australia; Safetycare Australia Pty. Ltd. ([Australia] : Safetycare Australia, 1989)
Shows how injuries arise in the workplace and emphasises the importance of safe work practices. Also emphasises the importance of prompt attention to injuries
Title from title screen
VCD format
Keywords: Tools; Industrial safety